SIMULATOR PEMBANGKIT LISTRIK TENAGA HYBRID: (PV, PLTMH, GENSET) - Gurning, Felix Andreas; Susilo, Susilo; Widodo, Bambang (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2025)
ABSTRACT Indonesia has a natural wealth that is quite suitable for producing electricity. At present, this country is very dependent on energy sources to diesel, gas and coal to run geothermal power facilities. However, because of the favorable equatorial position, Indonesia accepts the entry of consistent sunlight throughout the year, positioning it is better to utilize solar energy. In addition, a profitable wind pattern and regular rainfall in this country provide further opportunities for the construction of solar, wind and water power plants (PLTS, PLTB, and PLTPH). Considering the community's need for electrical energy is increasing and the distribution of electricity has not been evenly distributed to all regions, this hybrid system power plant will greatly help the community if this hybrid system can be applied directly. This study aims to develop hybrid power generation simulations, offering alternative energy solutions through the integration of three different types of generators: Photvoltaic (PV), Micro-hydro power (MHP), and conventional generators. This hybrid regulation uses a series of coordinated systems involved to improve the efficiency of production and power distribution. In this study the voltage results were 134.01 V and a current of 0.029 A for an 8 watt load, for a load of 18 watts of 132.58 V with a current of 0.056 A and for a load of 23 watt of 131.49 watts with a current of 0.0781 A.